2020
DOI: 10.1177/1753425920949917
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan derived from Lactobacillus rhamnosus MLGA up-regulates the expression of chicken β-defensin 9 without triggering an inflammatory response

Abstract: Defensins are critical components of the innate immune system and play an important role in the integration of innate and adaptive immune responses. Although information on the immunomodulatory properties of peptidoglycan from bacteria is abundant, little is known about the β-defensin induction effect of peptidoglycan from the probiotic Lactobacillus. This study investigated the effect of intact peptidoglycan from L. rhamnosus MLGA on the induction of avian β-defensin 9 in chicken immune cells and intestinal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…It has been repeatedly confirmed that lactobacilli produce metabolites that suppress the growth of Salmonella [28][29][30]. Lactobacilli also produce metabolites affecting host gene expression [31,32]. We have also reported that whenever lactobacilli overgrow, they efficiently suppress growth of other gut microbiota members [15].…”
Section: Discussionmentioning
confidence: 69%
“…It has been repeatedly confirmed that lactobacilli produce metabolites that suppress the growth of Salmonella [28][29][30]. Lactobacilli also produce metabolites affecting host gene expression [31,32]. We have also reported that whenever lactobacilli overgrow, they efficiently suppress growth of other gut microbiota members [15].…”
Section: Discussionmentioning
confidence: 69%
“…However, it is well known that long-term and excessive use of antibiotics can lead to problems such as pathogen drug resistance and antibiotic residues ( Ye et al., 2007 ). Probiotics are promising antibiotic substitutes, that can inhibit the growth and reproduction of pathogenic bacteria ( Nakphaichit et al., 2019 ), regulate immunity ( Huang et al., 2020 ), enhance intestinal barrier function, and promote the balance of intestinal microbiota ( Zhang et al., 2021 ). Screening for probiotics that can inhibit S. Enteritidis is expected to eliminate the disadvantages of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…reuteri I5007 could enhance the HDPs via increasing colonic butyric acid production and activating peroxisome proliferator-activated receptor γ (PPAR-γ) and G-protein-coupled receptor 41 (GPR41) or downstream molecules but not intestinal microbiota structure changes Lactobacillus rhamnosus MLGA dose-dependently promoted avian β-defensin 9 mRNA expression in chicken PBMCs and splenocytes without activation of the expression of pro-inflammatory cytokines interleukin (IL)-1b, IL-8, and IL-12 Lactobacillus plantarum ZLP001 induced porcine HDP expression in vivo and in vitro , providing a promising approach to improve intestinal health and enhance diarrhea resistance in weaning piglets …”
Section: Regulation Of Hdp Expressionmentioning
confidence: 99%